Alcohol and pregnancy (Portuguese Journal of Family Medicine and General Practice, 2008)
World Health Organization considers pregnant and suckle women shoud not drink alcohol at all.Most women drink alcohol without knowing their pregnangy. Drinking alcohol while pregnant may produce irreversible physical, cognitive and behaviour disturbances in the growing embryo. The worse disease related with alcohol abuse is known as Fetal Alcohol Syndrome characterized by: late growing before and after birth, nervous system envolvement, late psycomotor development, QI and behaviour disturbance and facial dismorphysm. At least two of the physical signs must be present as microcephaly, microphtalmy, small palpebral fissure, hypoplasy of nasal sept with thin superior lip and maxillary hypoplasy. Other consequences of alcohol drinking during pregnancy are the Alcohol Realted Neurodevelopmental Disorder and the Alcohol Related Birth Defects. The prevention of these diseases is obtained with total abstinence of alcohol drinking while pregnant.
Keywords: Pregnancy; Alcohol; Alcohol Fetal Syndrome